Constitutional and Ethical Dilemmas in Gender Affirmative Care in Children with Gender Dysphoria - Alfarisi, Achmad Hasan; Abdi, Rahmat Wildan Safari (Civiliza Publishing, 2025)
Gender dysphoria occurs not only in adults, but also in children under the age of majority. Their inner belief that their gender identity is not aligned with their physical body causes a desire to change their physical appearance through treatments that affirm their gender identity. Examples include genitoplasty, puberty blockers, and cross-sex hormone therapy. Proponents argue that these desires should be accommodated because everyone, including children, has the right to determine what can be done to their own bodies. In addition, some findings suggest that these treatments can provide positive psychological benefits for these children. On the other hand, opponents question whether the consent given by children who want such treatments is valid. In addition, providing irreversible medical treatment simply to affirm gender identity can have physiological and psychological impacts. So instead of affirming the wishes of these children, medical doctors should focus on saving them from irreversible medical actions. This discourse is carried out by considering the child's rights proportionally, which needs to be balanced by ensuring their knowledge and maturity in making decisions. Keywords: children, gender dysphoria, gender affirmative care, constitutional obligations